And the Spirit Moved Them: The Lost Radical History of America's First Feminists. - Mattalia, Glendy X. (Booklist, 2017)
A review of the book "And the Spirit Moved Them: The Lost Radical History of America's First Feminists," by Helen LaKelly Hunt, is presented.